2020
DOI: 10.1002/jlb.2a0520-321rr
|View full text |Cite
|
Sign up to set email alerts
|

PRDM1 decreases sensitivity of human NK cells to IL2-induced cell expansion by directly repressing CD25 (IL2RA)

Abstract: IL2 receptor signaling is crucial for human NK cell activation and gain of effector functions. The molecular mechanisms involved in termination of IL2 activation are largely unknown in human NK cells. PR/SET domain 1 was previously reported to decrease cell growth and increase apoptosis in an IL2-dependent manner in malignant NK cell lines, suggesting the possibility of down-regulation of IL2 signaling pathway gene(s) through direct transcriptional repression. Using ChIP-Seq, we identified a PRDM1 binding site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…In the current study, we noticed that IL-15 was superior to IL-2 in enhancing the NK cell cytotoxicity in vitro with all used protocols, except the continuous IL-2/15 expanded NK cells. The low CD25 expression, as seen here with the IL-2/15 expanded NK cells, has an impact on the NK cells' sensitivity to IL-2 (47,48). This is possibly related to the continuous presence of soluble IL-2, which inhibits the expression of the high affinity IL-2 receptor and its alpha chain (CD25) (47,48).…”
Section: Discussionmentioning
confidence: 66%
“…In the current study, we noticed that IL-15 was superior to IL-2 in enhancing the NK cell cytotoxicity in vitro with all used protocols, except the continuous IL-2/15 expanded NK cells. The low CD25 expression, as seen here with the IL-2/15 expanded NK cells, has an impact on the NK cells' sensitivity to IL-2 (47,48). This is possibly related to the continuous presence of soluble IL-2, which inhibits the expression of the high affinity IL-2 receptor and its alpha chain (CD25) (47,48).…”
Section: Discussionmentioning
confidence: 66%
“…This analysis revealed that interactions between monocytes and NK cells in severe COVID-19 were predicted to upregulate genes involved in NK cell cytotoxicity [ GZMB ( 48 ), PRF1 ( 49 ), LGALS1 ( 50 ), TNFSF10 ( 51 )], proliferation [ MCM6 ( 52 ), KNTC1 ( 53 )], apoptosis [ ANXA2 ( 54 ), ANXA5 ( 54 ), BAX ( 55 ), FAS ( 56 ), CASP1 ( 57 ), PML ( 58 )], cellular adhesion [ STMN1 ( 59 ), VCAN ( 35 )], and migration [ CX3CR1 ( 60 )]. Other predicted downstream targets in severe COVID-19 included several genes associated with decreased NK cell functionality [ EZH2 ( 61 ), PRDM1 ( 62 ), SERPINB1 ( 63 )], two STAT family transcription factors [ STAT1 , STAT2 ( 64 )], and signaling adaptor MYD88 ( 65 ) ( Fig. 2C ).…”
Section: Resultsmentioning
confidence: 99%
“… 14 , 28 , 29 Studies indicated IL-2Rα essential for the sensitivity of human NK cells. 30 Therefore, we speculated that simulating high-affinity IL-2Rαβγc trimeric receptor complexes would benefit NK cell activation and persistence. In parallel, to limit the systemic toxicity of IL-2, we constructed a cell-restricted mbIL-2 by fusion of human IL-2 and human IL-2Rα with a (G 4 S) 3 linker.…”
Section: Discussionmentioning
confidence: 99%
“… 14 , 28 , 29 However, the low-affinity receptor IL-2Rα is essential for the sensitivity of human NK cells. 30 To simulate the biological process of high-affinity trimeric receptor complex in NK cells and avoid the side effects caused by IL-2, we constructed a cell-restricted artificial IL-2, named membrane-bound IL-2 (mbIL-2), by fusion of human IL-2 and human IL-2Rα with a (G 4 S) 3 linker. Here, we demonstrated that mbIL-2 can vigorously improve NK-92 cell survival and proliferation, as well as enhance NK-92 cell-mediated antitumor activity by tuning IL-2 receptor downstream signals and NK cell receptor repertoire expression.…”
Section: Introductionmentioning
confidence: 99%